The effect of fish oil supplementation on resistance training-induced adaptations - Jeffery L. Heileson; Steven B. Machek; Dillon R. Harris; Sara Tomek; Leticia C. de Souza; Adam J. Kieffer; Nicholas D. Barringer; Andrew Gallucci; Jeffrey S. Forsse; LesLee K. Funderburk (Taylor & Francis Group, 2023)
Background Resistance exercise training (RET) is a common and well-established method to induce hypertrophy and improvement in strength. Interestingly, fish oil supplementation (FOS) may augment RET-induced adaptations. However, few studies have been conducted on young, healthy adults. Methods A randomized, placebo-controlled design was used to determine the effect of FOS, a concentrated source of eicosapentaenoic acid (EPA) and docosahexaenoic acid (DHA), compared to placebo (PL) on RET-induced adaptations following a 10-week RET program (3 days·week−1). Body composition was measured by dual-energy x-ray absorptiometry (LBM, fat mass [FM], percent body fat [%BF]) and strength was measured by 1-repetition maximum barbell back squat (1RMSQT) and bench press (1RMBP) at PRE (week 0) and POST (10 weeks). Supplement compliance was assessed via self-report and bottle collection every two weeks and via fatty acid dried blood spot collection at PRE and POST. An a priori α-level of 0.05 was used to determine statistical significance and Cohen's d was used to quantify effect sizes (ES). Results Twenty-one of 28 male and female participants (FOS, n = 10 [4 withdrawals]; PL, n = 11 [3 withdrawals]) completed the 10-week progressive RET program and PRE/POST measurements. After 10-weeks, blood EPA+DHA substantially increased in the FOS group (+109.7%, p< .001) and did not change in the PL group (+1.3%, p = .938). Similar between-group changes in LBM (FOS: +3.4%, PL: +2.4%, p = .457), FM (FOS: −5.2%, PL: 0.0%, p = .092), and %BF (FOS: −5.9%, PL: −2.5%, p = .136) were observed, although, the between-group ES was considered large for FM (d = 0.84). Absolute and relative (kg·kg [body mass]−1) 1RMBP was significantly higher in the FOS group compared to PL (FOS: +17.7% vs. PL: +9.7%, p = .047; FOS: +17.6% vs. PL: +7.3%, p = .011; respectively), whereas absolute 1RMSQT was similar between conditions (FOS: +28.8% vs. PL: +20.5%, p = .191). Relative 1RMSQT was higher in the FOS group (FOS: +29.3% vs. PL: +17.9%, p = .045). Conclusions When combined with RET, FOS improves absolute and relative 1RM upper-body and relative 1RM lower-body strength to a greater extent than that observed in the PL group of young, recreationally trained adults.